Pola Kepemimpinan Orang Tua Dalam Mendidik Anak Didalam Keluarga (Studi Kasus : Montong Belandeng Dusun Ganti 1 Desa Ganti Kecamatan Praya Timur Lombok Tengah) - Rusandi, Haeruman; Mukhlisin Asyrafuddin, Nurul; Makky, Khalid (Progressive of Cognitive and Ability, 2023)
This research examines the leadership patterns of parents in educating children in the family in Montong Belandeng Dusun Ganti I, Ganti Village, East Praya District, Central Lombok. Apart from that, this research also examines how parents lead the family in Montong Belandeng, Ganti I Hamlet, Ganti Village, East Praya District, Central Lombok. This research uses descriptive qualitative research. By using data collection techniques in the form of observation, interviews and documentation. The aim of this research is to understand the form of parental leadership in educating children in Montong Belandeng Dusun Ganti I Ganti Village, and also to understand how parents lead in the family in Montong Belandeng Dusun Ganti I Ganti Village. The analysis used in this research refers to analysis according to Sugiyono, the research procedures are: data reduction, data display, and data validation. The research results obtained from this research are that the leadership pattern of parents in educating children in Montong Belandeng Dusun Ganti I, Ganti Village is a permissive leadership pattern and parents lead by giving children the freedom to do whatever they want